Practice makes perfect statistics - McCune, Sandra (McGraw-Hill Education, 2010)
Practice Makes Perfect: Statistics is not focused on any particular test or exam, but complementary to most statistics curricula. Because of this approach, the book can be used by struggling students needing extra help, readers who need to firm up skills for an exam, or those who are returning to the subject years after they first studied statistics. Its all-encompassing approach will appeal to both U.S. and international students.